Effect of plasticizer and curing system on freezing resistance of rubbers. Issue 2 (20th August 2013) - Oh, Jaeho; Yoo, Yong Hwan; Yoo, Il‐Sou; Huh, Yang‐Il; Chaki, Tapan Kumar; Nah, Changwoon
ABSTRACT At glass transition temperature, Tg the rubber compound becomes stiff and brittle and it loses all its rubbery characteristics. This article deals with the changes in Tg of rubber blends based on natural rubber and polybutadiene rubber of varying vinyl content having different types and content of plasticizers, different curing systems and its effect on physico‐mechanical properties to improve its freezing resistance. The plasticizers used were dioctylphthalate (DOP), tricrecylphosphate (TCP), dioctyladipate (DOA), and oil type plasticizers like parafinic oil (P#2) and aromatic oil (A#2). Among the plasticizers, when DOP and DOA content was high, an appreciable decrease of Tg was found compared to TCP. Moreover, there was a remarkable decrease of Tg using DOA plasticizer, which shows more effective on freezing resistance. However, there was not much change in Tg with oil‐type plasticizers with high oil content compared to TCP plasticizer. The effect of cross‐linking systems such as conventional sulfur vulcanization (CV), efficient sulfur vulcanization (EV), and dicumyl peroxide (DCP) and rubber blends with varying vinyl content in polybutadiene rubber were also carried out. It was found that Tg in different cross‐linking system decreased in this order: CV < EV < DCP. It reveals that DCP cross‐linking system affect more for improving freezing resistance. Physico‐mechanical properties such as tensile strength, tear strength, hardness were also measured. The ratio of initial slope (M0) to steady‐state slope (M1), M0/M1 in tensile curves of different blends were verified, which in turn related to the physico‐mechanical properties and freezing resistance of rubber compounds. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39795.